Cross-Sectional and longitudinal associations of objectively-measured physical activity on blood pressure: evaluation in 37 countries - Mehdi Menai (Health Promotion Perspectives, 2017)
Background: We examined the cross-sectional and longitudinal associations of objectively measured physical activity (step counts) and blood pressure (BP) among adults spanning 37countries.Methods: Across 37 countries, we used data from a pool of 9238 adult owners of Withings’ Pulse activity trackers, which measures steps taken each day, and Wireless Blood Pressure Monitor, which measures BP. Analyses were adjusted on age, sex, number of days where the tracker was worn, and number of BP measurements. Data was collected from 2009 to 2013.Results: Subjects had a mean ± standard deviation (SD) age of 51.6 ± 11.3 years and a body mass index (BMI) of 28.7±5.5 kg/m2. A 1-month increase of more than 3000 steps per day was associated with a decrease of systolic BP (SBP) and diastolic BP (DBP) among the obese (1.57mm Hg and 1.29 mm Hg respectively, both P<0.001) and the overweight population (0.79mm Hg and 0.84 mm Hg respectively, both P≤0.001), but not in the normal weight population(P=0.60 and P=0.36 respectively).Conclusion: One-month increases in daily step counts was associated with a decrease of SBP and DBP in a large obese and overweight free living population.